Medicinal Plant - Mentha Asiatica - Usmonova Gulshod Ibrohimovna; Karimova Lobar Fatullayevna; Khalmetova Fatima Yudashbekovna; Achilova Gulrukhsor Azamatovna (Genius Journals, 2023)
Currently, the study of medicinal plants, their effect on diseases, preparation of medicines from them are relevant topics. This article provides the latest information about the botanical classification, importance, medicinal properties and use of mint, one of the medicinal plants, in folk medicine
Keywords: Medicinal plants; alkaloids; glycosides; essential oils